Variable penetration rate testing for shear strength of peat – a review - Akeem, Gbenga Amuda; Fauzan, Sahdi; Alsidqi, Hasan; Siti Noor Linda, Taib (Taylor & Francis Ltd., 2018)
This paper presents a review of the advances in the variable penetration rate testing methods on inorganic soils and its potentials to investigate the appropriate penetration rate and resistance factors for penetrometer testing of peat. A partially drained condition, which often leads to misinterpretation of test results, has been observed in peat penetration testing when the standard rate of 20 mm/s is used. Although the impact of rate-effects on penetration resistance measured with CPTu, T-bar and ball penetrometer have been investigated extensively in various intermediate soils, research is limited on how penetration rate controls drainage conditions and affects consolidation behaviour in peat. This review synthesises research developments in using variable penetration rate tests. The objective is to evaluate the transition of drainage conditions and consolidation behaviour of inorganic soils while focusing on its adaptability for peat. The review provides guidance on the investigation of the penetration rate testing in peat